Outside-In Blended Learning: A Transformative Approach to Developing Mathematical Critical Thinking Skills - Asri Ode Samura; Arwan Muhammad Said; Rusdyi Habsyi; Ila Ali Rauf (Universitas Syiah Kuala, 2025)
Developing students mathematical critical thinking skills is essential for addressing complex problems in contemporary mathematics education. This study examines the effects, differences, and improvement levels of students mathematical critical thinking skills through the implementation of Outside-In Blended Learning and conventional instruction. A quasi-experimental method with a nonequivalent control group design was employed. The population consisted of eighth-grade students at State Junior High School 1 South Halmahera, Indonesia, with a total sample of 78 students. Data were collected using a mathematical critical thinking skills test and analyzed through inferential statistics. The findings indicate that both Outside-In Blended Learning and conventional instruction positively influenced students mathematical critical thinking skills. Through the Outside-In Blended Learning model, students engaged with contextual problems by observing, interpreting, and constructing solutions based on conceptual understanding reinforced during classroom discussion and reflection. In contrast, teacher-centered instruction provided fewer opportunities for exploration and reasoning. A clear gap emerged between the two groups, suggesting that conventional instruction does not fully optimize students potential for critical thinking, whereas Outside-In Blended Learning more effectively promotes analytical and reflective thinking. The improvement in students mathematical critical thinking after the implementation of Outside-In Blended Learning was categorized as moderate, with an N-gain score of 54.93. Overall, the Outside-In Blended Learning model offered a more comprehensive and contextual influence on students mathematical critical thinking development